PELAKSAAN PROMOSI HOTEL SAPADIA DI KABUPATEN ROKAN HULU PROVINSI RIAU - Irma Putri Oktaviani; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Implementation of promotion is efforts conduted by company in order to advising, informing about their product and company is good in te form of service and also product of finished goods middle of social life, consumer of client, so that the product become recognized and used by costumer with all the form of amenity and advantage facility of given promotion. This research conducted at Sapadia hotel Rokan Hulu, at Tuanku Tambusai street. The purpose of this research is to implementation of promotion at Sapadia hotel Rokan Hulu. In this research is methodologies used by descriptive, sample used by that visitor of Sapadia hotel Rokan Hulu and as source of information is sales and marketing manager. Data collecting is through interview, observation, questioner and documentation. From result implementation of promotion conducted by Sapadia hotel Rokan Hulu convering advertisement activity advertising, personal selling, sales promotion, merchandising and public relation, expressing that the promotion activity be at very good.  Keywords : Implementation, Promotion, Hotel